The Relationship Between Ankle Proprioception and Functional Mobility in People With Parkinson's Disease: A Cross-Sectional Study - Wang, Yejun; Witchalls, Jeremy; Preston, Elisabeth; Wang, Zhen; Zhuang, Jie; Waddington, Gordon; Adams, Roger; Han, Jia (Frontiers in Neurology, 2021)
Previous research has found ankle proprioception to be impaired in people with Parkinson’s disease (PD). However, the relationship between ankle proprioception and functional mobility in people with PD has not been fully investigated. The purpose of this study was to examine whether ankle proprioception is related to the functional mobility of people with PD. Forty-two participants with mild to moderate PD volunteered. Ankle proprioceptive acuity was measured in standing, by using active movement extent discrimination assessment (AMEDA). Functional mobility measures included the timed-up-and-go test (TUG), 30 seconds sit-to-stand test (30s-STS) and 10-meter walking test (10MWT). Step length and step cadence were recorded during the 10MWT. No significant correlation was found between ankle proprioceptive discrimination scores and any mobility performance measure in people with PD. However, ankle proprioception scores were significantly correlated with step length and step cadence, and were significantly and negatively correlated with the stage of modified Hoehn and Yahr. The lack of relationship between ankle proprioceptive acuity and functional mobility in PD suggests that people with PD may be more limited by reduced sensorimotor integration or may rely more on other sensory input, rather than ankle proprioception, to achieve functional mobility, a finding consistent with sensory reweighting theory. In addition, poorer ankle proprioceptive acuity was associated with decreased step length and increased step cadence, suggesting that the shuffling gait observed in PD may be related to impaired ankle proprioception, which has important clinical implications for gait retraining in people with PD. Given that ankle proprioception was significantly and negatively correlated with the stage of modified Hoehn and Yahr, it may warrant being used as an objective biomarker to monitor the progression of PD.